The Comparative Study of Three Types of KKU Coaxial Circle Circuits - Sumret, Krisana; Sathitkarnmanee, Thephakorn; Chau-In, Waraporn (Srinagarind Medical Journal, 2013)
Background : The KKU coaxial circle circuits, which have been used in Srinagarind hospital since 1994, are simply constructed from available materials in the operating theatre. They are 100-120 cms long, light weight that make them easy and convenient to use. This study call them type II. The other types in this study are different in length, there are 70 and 150 cm long, called type I and type III respectively. In case control study arterial blood gases of 3 types of circuit in all surgical patients. Statistical significance was set at the 0.05 level. The paired t-test was used to determine if there were any differing values adjusting for study effects. Objective : To use either the short or long circuit in appropriate surgery. Design : Experimental study. Setting : The study was done at operating room in Srinagarind Hospital. Subjects : The study was done in 30 surgical patients of Srinagarind Hospital, who have physical status I. The mean age and body weight were 32.97 ± 10.33 yrs and 55.27 ± 7.81 kgs respectively. The circuits were used in patients who were operated under general anesthesia with controlled ventilation. Intervention : N.A Measurements : Total gas flow, tidal volume and respiratory rate were fixed at 6 lpm (N2O:O2=4:2), 10 ml/kg and 12 bpm respectively. The study was started with type I then changed to type II and type III at interval of 20 minutes. Arterial blood gases were analysed at time 20 minutes after the use of each circuit. Results : The result between type I and type II had no significant difference for pH, pCO2,pO2 and O2 saturation. But for type II and type III, they were significantly different in pO2